If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27 = 18x Solving 27 = 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 27 + -18x = 18x + -18x Combine like terms: 18x + -18x = 0 27 + -18x = 0 Add '-27' to each side of the equation. 27 + -27 + -18x = 0 + -27 Combine like terms: 27 + -27 = 0 0 + -18x = 0 + -27 -18x = 0 + -27 Combine like terms: 0 + -27 = -27 -18x = -27 Divide each side by '-18'. x = 1.5 Simplifying x = 1.5
| z+5=-1 | | 3b+2g=10 | | 1/4t=12 | | 1.1s=-44 | | 8a=3 | | x^2=8.33333 | | 13(4x-10)=5x-3 | | 9.8x^2+8x=1400 | | 2(2x-10)=2(14-3X) | | 4y/=8 | | T+4.5=-3 | | 9.8x^2+8t=1400 | | 4p+7t-1p+5-5p=0 | | 50-6k=20 | | 3x/7=4/9 | | -3(1+4v)=30 | | 2.40=.20x+34y | | (-6)-3= | | 5(2x-1)+x+17=5x+6 | | (-3x^3+x^2-11)-(-4x^3-3x^2+1)= | | 8+3q=44 | | 2g+14=36 | | 0=-1000(x-7.7) | | 5!3!/6! | | 5/7x-10=-60 | | 4g+5=17-2g | | 7700=-1000(x-7.7) | | X+.75y=37 | | 1.5k+4=6 | | 7+6(1-8x)=15 | | 3(4+5g)=0 | | 3x+10=71 |